Psychometric validation of Social Physique Anxiety Scale for Brazilian people with limb amputee - Ferreira Filho, Roberto Gomes; Neves, Angela Nogueira (Acta Fisiátrica, 2020)
Physical-social anxiety is about the sensation of discomfort experienced when there is a real or imagined situation, in which part or the whole body is exposed to the judgment of another person. To verify the factorial structure of the Brazilian version of the Social Physique Anxiety Scale in a reference sample of amputees. Confirmatory factor analysis was performed with data obtained from a sample of 100 participants, 99% of whom were men, with an average age of 48.26 (± 18.26; max= 82; min= 15) years, and time average amputation of 76.36 (± 95.36; max= 504; min= 1) months, to determine the best fit between the one-dimensional and two-dimensional models. Construct reliability values and Conbrach's alpha test were calculated to determine evidence of reliability. For construct validity, evidence of convergent and discriminant validity was generated. Evidence of convergent validity was generated by the average extracted variance (AVE) and by the analysis of the correlation with a similar construct measure. For the discriminant validity, it was verified if there was a theoretically expected difference between two groups. The model with the best fit was the one-dimensional model after the elimination of four items (RMSEA= 0.074, χ2/df= 1.54, CFI= 1, NFI= 0.98, NNFI= 1, AGFI= 0.98, GFI= 0.99, AIC= 62.84). Evidence of internal and discriminant reliability was satisfactorily generated for the measurement model, with a caveat to convergent validity, with a low value of the extracted average variance.  The scale can be used in Brazil to assess physical and social anxiety in amputees.